The Role of Content Creators in Digital Marketing Communication: Trust Construction & Audience Engagement on Hiskara Studio’s Instagram Account - Virna Estriana; Rezky Pratami; Novita Intan (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2026)
This study examines content creator-based digital marketing communication strategies implemented by Hiskara Studio through Instagram and short-form video content to build consumer trust and engagement in architecture and interior design services. This industry represents a professional service sector that is technical, economically valuable, and strongly influenced by aesthetic perception, portfolio credibility, and the ability to translate consumer spatial needs into design solutions. These characteristics create communication challenges because consumers evaluate not only final design outputs, but also work processes, service transparency, and provider reliability. This research uses a qualitative case study design. Data were collected through systematic observation of the Instagram account @hiskara_studio, digital documentation, and thematic mapping of content related to portfolio presentation, design education, spatial visualization, and audience interaction. Data were analyzed using NVivo-assisted thematic analysis to identify visual communication patterns, content creator roles, trust formation, and consumer engagement. The findings show that Instagram functions as a visual showcase emphasizing design portfolios, professional identity, and brand aesthetics, while short-form videos expand reach through design process narratives and accessible spatial explanations. Content creators act as communication mediators who transform technical architectural messages into personal, informative, and relevant visual narratives. This study contributes to digital marketing communication scholarship by extending discussion from consumer goods sectors to architecture and interior design as trust-intensive professional services, and by offering practical directions for transparent and interactive platform-based communication.